2015
DOI: 10.1152/ajprenal.00197.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of NHE3 and SGLT1 by the circadian clock protein Per1 in proximal tubule cells

Abstract: We have previously demonstrated that the circadian clock protein period (Per)1 coordinately regulates multiple genes involved in Na(+) reabsorption in renal collecting duct cells. Consistent with these results, Per1 knockout mice exhibit dramatically lower blood pressure than wild-type mice. The proximal tubule is responsible for a majority of Na(+) reabsorption. Previous work has demonstrated that expression of Na(+)/H(+) exchanger 3 (NHE3) oscillates with a circadian pattern and Na(+)-glucose cotransporter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…3). Pharmacological blockade of the circadian clock protein Per1 decreases the expression of both NHE3 and SGLT1 not only in the renal cortex of mice, but in human proximal tubule cells as well [27]. These studies provide a useful foundation for further exploration into the role of the circadian clock in the proximal tubule, especially at the molecular level.…”
Section: Circadian Rhythms Along the Nephronmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Pharmacological blockade of the circadian clock protein Per1 decreases the expression of both NHE3 and SGLT1 not only in the renal cortex of mice, but in human proximal tubule cells as well [27]. These studies provide a useful foundation for further exploration into the role of the circadian clock in the proximal tubule, especially at the molecular level.…”
Section: Circadian Rhythms Along the Nephronmentioning
confidence: 99%
“…Both of these studies provide some insight into which clock genes may be playing a role in regulating kidney function in diabetes. A recent study by Solocinski et al has shown that Per1 regulates the expression levels of SGLT1, but not SGLT2, in the proximal tubule of 129/sv mice and human proximal tubule (HK-2) cells [27], suggesting that Per1 regulates glucose transport in the kidney. In the diabetic state, the up regulation of Per1 seen in both models of diabetes [186,187] may be contributing to the renal damage at the transcriptional level.…”
Section: Pathologies Associated With Impaired Circadian Rhythmsmentioning
confidence: 99%
“…Gumz et al provided the link between the clock and the epithelial sodium channel ENaC with the finding that PER1 transcriptionally regulates αENaC (Gumz et al, 2009). Subsequent studies provided further evidence that PER1 coordinately regulates several genes encoding proteins that function in renal sodium reabsorption (Solocinski et al, 2015, Richards et al, 2014c, Richards et al, 2014d). Global loss of Per1 on the hypertensive, salt-sensitive 129/sv mouse strain resulted in significantly reduced BP compared to wild type (WT) controls on a normal diet (Stow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…29, 30 Moreover, the significance of blood pressure rhythms in human disease is highlighted in human conditions where rhythms are absent, as in non-dipper hypertensive patients 31 that exhibit a raised incidence of cardiovascular morbidity. 32 Moreover, the prevalence of non-dipping blood pressure is not trivial, but may be up to 45% in humans 33 and may even further impact individuals with HIV 34 while targeting non-dipping blood pressure with night-time administration of antihypertensives may even be beneficial in diabetes.…”
mentioning
confidence: 99%